2009
DOI: 10.1007/s10571-009-9381-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liver Ischemia–Reperfusion Injury on the Activity of Neurons in the Rat Brain

Abstract: Liver ischemia-reperfusion injury (LIRI) influences different body cells. Little is known about the effect of LIRI on the activity of neurons. Response of neurons to: (1) single ligation of hepatic artery (LIRIa) for 30 min and (2) combined ligation of portal triade (common hepatic artery, portal vein, common bile duct, LIRIb) for 15 min was investigated in Wistar rats. Ninety minutes, 5 h, and 24 h after liver reperfusion, alanine aminotransferase (ALT) and aspartate aminotransferase (AST), interleukin 1alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Besides, accumulating studies of cerebral stroke, ischemia, or hemorrhagic have reported that the selective inhibitor of caspase-1, AC-YVAD-CMK, was proved to have a therapeutic effect and pyroptosis was involved in the pathophysiological process [40, 4951]. A previously published study found that the activity of cells in specific brain structures, anatomically or functionally associated with the liver, was reflected by Fos immunoreactivity and showed an increase under HIRI condition [52]. Besides, IL-1 β administration could also increase neuronal activations, which was showed by Fos immunoreactivity [53].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, accumulating studies of cerebral stroke, ischemia, or hemorrhagic have reported that the selective inhibitor of caspase-1, AC-YVAD-CMK, was proved to have a therapeutic effect and pyroptosis was involved in the pathophysiological process [40, 4951]. A previously published study found that the activity of cells in specific brain structures, anatomically or functionally associated with the liver, was reflected by Fos immunoreactivity and showed an increase under HIRI condition [52]. Besides, IL-1 β administration could also increase neuronal activations, which was showed by Fos immunoreactivity [53].…”
Section: Discussionmentioning
confidence: 99%
“…The parasympathetic nerves innervating the liver originate from the pre-ganglionic neurons in the dorsal motor nucleus of the vagus (DMV) located in the dorsal brainstem, however, no clear intrahepatic post-ganglionic neurons have been identified (Berthoud 2004). Previously we have shown (Pirnik et al 2009) that both models of LIRI activate Fos in a number of neurons in different brain structures. However, they are prominently activated mainly in the PVN, SON, and NTS/A2 and A1/C1 areas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this research was to extend our previous data (Pirnik et al 2009) dealing with mapping the anatomical distribution of Fos expression in response to LIRI by employing a dual Fos/neuropeptide immunohistochemistry. Our attempt was to perform a targeted phenotypic neuronal detection in several brain areas related to the liver functioning in male Wistar rats after 90 min, 5, and 24 h of: (i) a single ligation of the hepatic artery for 30 min and (ii) combined ligation of the portal triad (the common hepatic artery, portal vein, and common bile duct) for 15 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation